2013
DOI: 10.1097/acm.0b013e31827bfc0a
|View full text |Cite
|
Sign up to set email alerts
|

Making July Safer

Abstract: An SBML boot camp allows for individualized training, assessment, and documentation of competence before interns begin providing medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(47 citation statements)
references
References 33 publications
0
46
0
1
Order By: Relevance
“…Our results support the results of other studies in this area. Cohen, et al reported that a simulation-based mastery learning boot camp for internal medicine interns improved clinical skills scores on five parts of a clinical skills examination as compared to historical controls [13]. Krajewski, et al found that a two-month boot camp curriculum consisting of knowledge-based and procedural skills sessions, completion of web-based self-study modules, and standardized patient clinical skills assessments resulted in better patient care, procedural skills, and self-confidence compared with the previous year's interns, as judged by the teaching faculty [14].…”
Section: Discussionmentioning
confidence: 99%
“…Our results support the results of other studies in this area. Cohen, et al reported that a simulation-based mastery learning boot camp for internal medicine interns improved clinical skills scores on five parts of a clinical skills examination as compared to historical controls [13]. Krajewski, et al found that a two-month boot camp curriculum consisting of knowledge-based and procedural skills sessions, completion of web-based self-study modules, and standardized patient clinical skills assessments resulted in better patient care, procedural skills, and self-confidence compared with the previous year's interns, as judged by the teaching faculty [14].…”
Section: Discussionmentioning
confidence: 99%
“…Mastery learning techniques in the classroom have improved student knowledge of physics (Wambugu & Changeiywo, 2008) and computer science (LeJeune, 2010). In the field, mastery learning techniques have improved medical student clinical skills (Barsuk et al, 2012; Cohen et al, 2013; McGaghie, Issenberg, Cohen, Barsuk, & Wayne, 2011). Despite its effectiveness, mastery learning is not commonly used because variations in time to complete lessons and the need for individualized instruction make it difficult to incorporate into a traditional classroom setting (Cook, Brydges, Zendejas, Hamstra, & Hatala, 2013) (Bloom, 1968).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have revealed that, compared to traditional clinical education, simulation-based learning (SBL) with deliberate practice (DP) is significantly more effective toward acquiring specific clinical skills (McGaghie et al, 2011). SBL put participants into lifelike experiences where they are required to use the skill being taught (McGaghie et al, 2011;Cohen et al, 2013). DP involves a task with well-defined goals that learners are equipped to meet, and are motivated to focus on and repeatedly practice while receiving feedback and evaluation both during and following the practice (McGaghie et al, 2011).…”
Section: Introductionmentioning
confidence: 99%